Learning Foreign Language: Between Globalization and Hegemony in Indonesia - E. Sulyati (GoAcademica Research & Publishing, 2020)
Implementation of foreign language learning in Indonesia is an effort for the Indonesian people to be able to absorb and follow the development of science and technology in the world, as well as a way to get into the global society. Behind this goal, there is a concern about the infiltration of (Western) values that can erode the identity of foreign language learners as Indonesian. This concern arises because in learning foreign languages contained information about foreign culture (Western) and its cultural values. Western cultural values, if not critically viewed by foreign language teachers and learners, are very likely to change the cultural outlook of learners in Indonesia. Foreign language learning is even suspected of being a Western means of doing hegemony towards the people of Indonesia (East). In this article explained about the situation of foreign language learning in Indonesia, forms of